2004
DOI: 10.1158/0008-5472.can-03-3667
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation of EphB2 Receptor Regulates Migration and Invasion of Human Glioma Cells

Abstract: Eph receptor tyrosine kinases and their ligands, ephrins, mediate neurodevelopmental processes such as boundary formation, axon guidance, vasculogenesis, and cell migration. We determined the expression profiles of the Eph family members in five glioma cell lines under migrating and nonmigrating conditions. EphB2 mRNA was overexpressed in all five during migration (1.2-2.8-fold). We found abundant EphB2 protein as well as strong phosphorylation of EphB2 in migrating U87 cells. Confocal imaging showed EphB2 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(165 citation statements)
references
References 40 publications
11
153
0
1
Order By: Relevance
“…Bruce et al have identified aberrant EphA5 expression and showed that activation of EphA5 does not promote cell proliferation in glioma cell line (34). Nakada et al reported phosphorylation of R-Ras associated with EphB2 effects on glioma cell adhesion, growth, and invasion (20,35). Recently, EphA2 elevated in glioblastoma multiforme stimulated by ephrin-A1 was reported to induce an inhibitory effect on the growth and invasiveness of glioblastoma multiforme cells (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruce et al have identified aberrant EphA5 expression and showed that activation of EphA5 does not promote cell proliferation in glioma cell line (34). Nakada et al reported phosphorylation of R-Ras associated with EphB2 effects on glioma cell adhesion, growth, and invasion (20,35). Recently, EphA2 elevated in glioblastoma multiforme stimulated by ephrin-A1 was reported to induce an inhibitory effect on the growth and invasiveness of glioblastoma multiforme cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widely observed phenomenon of Eph receptor overexpression, their role has not been fully elucidated in the process of malignant phenotypes. However, recent bodies of evidence have implicated Eph involvement in the tumor progression of human cancers including malignant gliomas (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, malignant gliomas have unique features in their infiltration process, in which the tumor cells preferentially move along established tracts such as vascular basement membranes and myelinated axons (Hoelzinger et al, 2007). Axon guidance molecules such as ephrin-B3 (Nakada et al, 2006) and Slit2 (Mertsch et al, 2008) and their receptors (Nakada et al, 2004) have been implicated in the invasive behavior of gliomas, suggesting that GBM dispersal may involve the activation of dormant cell motility programs used during neural development.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, collectively, IL-13RA2, EphA2, and EphA3 are expressed in several GBM compartments documented to be involved in tumor progression and/or resistance to therapies (18,19). Of importance, ephrin-A5 (eA5) binds EphA2 and EpA3 receptors and also the EphB2 (17,65,66) receptor, all present in abundance in GBM tumors, but not in normal brain. Here, we discuss the novel idea of targeting all four receptors with one pharmaceutical compound.…”
Section: Targeted Cytotoxic Therapy Of Gbmmentioning
confidence: 99%